Religion and urbanity online - Rau, Susanne; Rüpke, Jörg (De Gruyter reference, 2020)
"Religion and Urbanity Online is a project of the DFG-funded Humanities Centre for Advanced Studies "Religion and Urbanity: Reciprocal Formations" (FOR 2779), based at the Max-Weber-Centre of the University of Erfurt. Main Editors: Susanne Rau and Jörg Rüpke (Universität Erfurt, Germany)"